Citrobacter rodentium infection activates colonic lamina propria group 2 innate lymphoid cells. - Rita Berkachy; Vishwas Mishra; Priyanka Biswas; Gad Frankel (PLoS Pathogens)
Group 3 innate lymphoid cells (ILC3s) play a major role in protecting against infection with the enteric mouse pathogen Citrobacter rodentium (CR) used to model infections with enteropathogenic and enterohaemorrhagic Escherichia coli. ILC3s-secreted IL-22 induces secretion of IL-18, antimicrobial peptides and nutritional immunity proteins as well as activation of tissue regeneration processes. While ILC2s have traditionally been associated with immune responses to helminth infection and allergic inflammation via the production of type 2 cytokines (e.g. IL-4, IL-5, IL-9 and IL-13), more recently they have been implicated in protection against Clostridium difficile and Helicobacter pylori infections. Here we show that colonic lamina propria ILC2s expand in response to CR infection and secrete IL-4, IL-5 and IL- 13, which are involved in maintenance of the intestinal barrier function, tissue repair and mucus secretion. When stimulated with IL-18, and IL-33 as a control, colonic ILC2s from uninfected mice secreted type 2 cytokines. Injection of IL-18 binding protein (IL18 BP), at 2- and 3-days post CR infection, blocked expansion of ILC2s in vivo. While ILC2s do not expand in CR-infected Il22-/- mice, injection of IL-18 into Il22-/- mice at 2- and 3-days post CR infection triggered ILC2s expansion. Importantly, injection of anti-IL-13, at 2- and 4-days post CR infection, diminished local secretion of IL-10 and IL-22. These data show that ILC2s are activated in response to infection with an enteric Gram-negative pathogen. Moreover, stimulation with IL-18 plays a role in ILC2s expansion and secretion of type 2 cytokines, which may participate in shaping the local immunological landscape.